Role of ABO secretor status in mucosal innate immunity and H. pylori infection. - Sara Lindén; Jafar Mahdavi; Cristina Semino-Mora; Cara Olsen; Ingemar Carlstedt; Thomas Borén; Andre Dubois (PLoS Pathogens)
The fucosylated ABH antigens, which constitute the molecular basis for the ABO blood group system, are also expressed in salivary secretions and gastrointestinal epithelia in individuals of positive secretor status; however, the biological function of the ABO blood group system is unknown. Gastric mucosa biopsies of 41 Rhesus monkeys originating from Southern Asia were analyzed by immunohistochemistry. A majority of these animals were found to be of blood group B and weak-secretor phenotype (i.e., expressing both Lewis a and Lewis b antigens), which are also common in South Asian human populations. A selected group of ten monkeys was inoculated with Helicobacter pylori and studied for changes in gastric mucosal glycosylation during a 10-month period. We observed a loss in mucosal fucosylation and concurrent induction and time-dependent dynamics in gastric mucosal sialylation (carbohydrate marker of inflammation), which affect H. pylori adhesion targets and thus modulate host-bacterial interactions. Of particular relevance, gastric mucosal density of H. pylori, gastritis, and sialylation were all higher in secretor individuals compared to weak-secretors, the latter being apparently "protected." These results demonstrate that the secretor status plays an intrinsic role in resistance to H. pylori infection and suggest that the fucosylated secretor ABH antigens constitute interactive members of the human and primate mucosal innate immune system.